Medicine management skills for nurses - Boyd, Claire (Student survival skills series, 2013)
"Anxious about being let loose with the drug trolley? Worried you'll make a mistake? This handy book is an essential guide for all nursing students, enabling you to understand the theory and practice of drug administration. Medicine Management Skills for Nurses will be an invaluable tool to facilitate your confidence and competence.This essential guide explores the theory and practice of drug administration briefly and coherently, with 'test your knowledge' exercises and questions throughout to assess your learning. It also includes 'words of wisdom'- tips from real life students from their own experiences. Ideal for carrying to clinical placements and clinical areas, Medicine Management Skills for Nurses will be your essential guide to the subject area of drugs and medicine administration. Special features: - Pocket sized for portability - Clear, straightforward, and jargon-free - Takes away the fear of drugs and medicines management, making it approachable, easy and fun- Features tips and advice from real life nursing students - Ties in with the NMC standards for pre-registration education and the Essential Skills Clusters - Examples and questions based on real life nursing & healthcare examples "--Provided by publisher.